Evaluation of Aztreonam and Ceftazidime/Avibactam Synergism against Klebsiella pneumoniae by MALDI-TOF MS - Camila Mörschbächer Wilhelm; Everton Inamine; Andreza Francisco Martins; Afonso Luís Barth (MDPI AG, 2023)
Introduction: Resistance to carbapenems due to the co-production of NDM and ESBL or NDM and KPC is increasing. Therefore, combined therapy with aztreonam (ATM) plus ceftazidime/avibactam (CZA) has been recommended. Then, it is necessary to develop and evaluate fast and simple methods to determine synergism in vitro in microbiology laboratories. Objective: To develop a method to determine the synergism of ATM and CZA by MALDI-TOF MS (SynMALDI). Method: Klebsiella pneumoniae (n = 22) isolates with blaNDM and/or blaKPC genes were tested. The time-kill curve assay was performed for four isolates (three positives for blaNDM and blaKPC and one positive for blaNDM only). For SynMALDI, each isolate was incubated for 3 h in 4 tubes containing brain-heart infusion broth with the following: (1) no antibiotic; (2) ATM at 64 mg/L; (3) CZA at 10/4 mg/L; and (4) ATM at 64 mg/L plus CZA at 10/4 mg/L. After incubation, the bacterial protein extract was analyzed by MALDI-TOF MS, and the relative growth (RG) was determined for each isolate, considering intensities of the peaks of the bacterium incubated with antibiotic (tubes 2, 3, and 4) to the same bacterium incubated without antibiotic (tube 1), as follows: RG = IntensityWith antibiotic/IntensityWithout antibiotic. The combination was determined as synergistic when there was an RG decrease of 0.3 in the antibiotic combination in relation to the RG of the most active antibiotic alone. Results: The combination of ATM plus CZA proved to be synergic by time-kill curve assay. All isolates tested with the SynMALDI method also presented synergism. Conclusions: Detection of synergism for ATM plus CZA combination can be determined by MALDI-TOF MS, providing fast results in order to improve patient treatment.